Stroke Emergency Education among Diabetes Mellitus Patients in the Working Area of Puskesmas Martapura Barat, Banjar Regency - Meggy Wulandari Kai; Emilda Sari; Ferry Fadli Fratama (Yayasan Pendidikan Tanggui Baimbaian, 2026)
Stroke is the second leading cause of death and the third leading cause of disability worldwide. Patients with Diabetes Mellitus (DM) have a 1.8 times higher risk of recurrent stroke in men and 2.2 times higher in women. Based on data from Puskesmas Martapura Barat in 2025, this area recorded a high prevalence of DM, with most patients experiencing hypertension as a comorbidity. However, no prior education on stroke emergencies had been conducted. This condition may increase the risk of disability and mortality due to delays in stroke management. Therefore, educational and health empowerment–based interventions are needed. This Community Service Program aimed to improve the knowledge of DM patients regarding stroke emergency management through structured health education using posters and banners as educational media. The program was conducted in the working area of Puskesmas Martapura Barat, Banjar Regency, in May 2026, involving 30 DM patients as participants. The methods included a pretest, interactive health education sessions using PowerPoint presentations, posters, and banners, early stroke detection simulations using the SEGERA method, and a posttest. The effectiveness of the program was evaluated through improvements in pretest and posttest scores, which were analyzed descriptively. The results demonstrated a significant increase in participants’ understanding, with the mean pretest score improving from 58.4 to 85.6 in the posttest, representing a 46.6% increase. All DM patients were declared competent in performing early stroke detection simulations. This program is expected to promote a stroke-responsive community through continuous educational approaches and the empowerment of local community potential.